Numerical Stability of Integration Methods used in Cloth Simulation (Journal of Fiber Bioengineering and Informatics, 2018)
For better performance, efficient numerical methods describing physical behaviour of clothes are needed for any cloth simulation system. In this paper we report a quantitative research performed on the stability of the most widely used integration techniques in cloth simulation. Advantages and weaknesses of various integration techniques are listed for trade-off among stability, accuracy and speed. In this light, we offer a solution for choosing numerical methods when dealing with simulation problems.